PENGARUH ONLINE CUSTOMER REVIEW DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ONLINE LAZADA - Nazla Audria; Reminta Lumban Batu (Value : Jurnal Manajemen dan Akuntansi, 2022)
Lazada online store has diminished guests, the abatement in web-based shop guests at Lazada can be said that purchaser buying choices at Lazada are still less alluring to general society, so focus on the Lazada online store to limit shoppers changing to other web-based store site locales. The requirement for factors that further develop buying choices at Lazada online stores, including on the web client audit and e-administration quality factors. The reason for the review was to decide and break down the impact of 1, to decide the impact of online client surveys on buying choices. 2.To decide the impact of e-administration quality influence buying choices. 3.To figure out how large the concurrent impact between online client audit and e-administration quality on buying choices. The examination utilized quantitative strategies. The examination test was 269 respondents. The test is handled with the assistance of SPSS. In light of the aftereffects of the review that internet based client surveys impact buying choices at Lazada online stores, E-administration quality affects buying choices at Lazada online stores, the concurrent impact of online client audits and e-administration quality on buying choices on lazada online shop. Keywords: Online Customer Review, E-Service Quality and Purchase Decision. Abstrak Toko online lazada mengalami penurunan pengunjung, menurunnya pengunjung toko online di lazada ini dapat dikatakan keputusan pembelian konsumen di lazada ini masih kurang diminati kalangan masyarakat, maka di perhatikan kembali pihak toko online lazada untuk meminimalisir konsumen beralih ke situs website toko online lainnya. Persyaratan untuk faktor-faktor yang selanjutnya mengembangkan keputusan pembelian di toko online Lazada, termasuk online custemer review dan pengaruh e-service. Alasan peninjauan adalah untuk memutuskan dan memeriksa dampak 1. Untuk memutuskan dampak survei klien online terhadap keputusan pembelian. 2.Untuk memutuskan pengaruh e-service mempengaruhi keputusan pembelian. 3.Untuk mengetahui seberapa besar dampak sinkron antara online custemer review dan e-service quality pada keputusan pembelian. Eksplorasi menggunakan teknik kuantitatif. Uji eksplorasi sebanyak 269 responden. Tes ditangani dengan bantuan SPSS. Mengingat efek dari tinjauan bahwa online custemer review memengaruhi pilihan pembelian di toko online Lazada, e-service quality memengaruhi pilihan pembelian di toko online Lazada, dampak bersamaan dari online custemer review dan e-service quality pada keputusan pembelian di toko online Lazada. toko online lazada. Kata Kunci: Online Customer Review, E-Service Quality dan Keputusan Pembelian.